Dynamic changes of serum taurine and the association with gestational diabetes mellitus: A nested case-control study - Wang, Jia; Wang, Yuanyuan; Zheng, Wei; Yuan, Xianxian; Liu, Cheng; Zhang, Ya; Song, Wei; Wang, Xiaoxin; Liang, Shengnan; Ma, Xu; Li, Guanghui (Frontiers in Endocrinology, 2023)
Objective: There is a lack of risk factors that can effectively identify gestational diabetes mellitus (GDM) in early pregnancy. It is unclear whether serum taurine in the first trimester and dynamic changes have different characteristics in GDM women. Whether these features are associated with the occurrence of GDM has not yet been elucidated. The main objective of this study was to observe the dynamic changes of serum taurine during pregnancy and investigate the relationship between serum taurine levels and GDM in the first and second trimesters. Methods: This was a nested case-control study in 47 women with GDM and 47 age-matched normoglycemic women. We examined serum taurine at 8-12 weeks’ gestation and 24-28 weeks’ gestation. The serum taurine of the two groups was compared. Multivariable logistic regression analysis was performed to investigate how serum taurine was associated with GDM. Results: The serum taurine concentration of GDM women was significantly lower than that of normoglycemic women in the first trimester(2.29 vs 3.94 μmol/L, P<0.001). As the pregnancy progressed, serum taurine concentration in normoglycaemic women decreased significantly(3.94 vs 2.47 μmol/L, P<0.001), but not in the GDM group(2.29 vs 2.37 μmol/L, P=0.249), resulting in the disappearance of differences between the two groups(2.47 vs 2.37 μmol/L, P=0.160). After adjustment for pre-pregnancy body mass index(BMI), fasting plasma glucose(FPG), and lipid profiles in the first trimester, the serum taurine concentration in the first trimester was negatively correlated with the risk of GDM(OR=0.017, 95% CI=0.003-0.107, P<0.001). Furthermore, dynamic change of serum taurine showed a significantly positive correlation with the risk of GDM(OR=9.909, 95% CI=3.556-27.610, P<0.001). Conclusions: Low serum taurine concentration in the first trimester was significantly associated with the development of GDM. As the pregnancy progressed, the association between serum taurine and GDM disappeared in the second trimester, which might be related to the inhibition of taurine transporter(TauT) activity by high glucose.